Innovative Approaches for the Sedimentological Characterization of Fine Natural and Anthropogenic Sediments in Karst Systems: The Case of the Apuan Alps (Central Italy) - Nannoni, Alessia; Piccini, Leonardo; Costagliola, Pilario; Batistoni, Nicolò; Gabellini, Pietro; Cioni, Raffaello; Pratesi, Gabriele; Bucci, Silvia (Frontiers in Earth Science, 2021)
The Apuan Alps (NW Tuscany) is an important area of Central Italy characterized by large karst systems mainly fed via direct and diffuse water infiltration (autogenic recharge). These waters usually transport a clastic sediment load, originated by natural, surface and subsurface rock erosion/weathering which, in part, is deposited underground. In the Apuan Alps, during extreme rain events, huge amounts of carbonate powder, produced as a waste resulting from the quarrying operations of the famous “Carrara” marble, mix up with meteoric waters forming a slurry that is transported through the karst openings into the caves, where the carbonate powder may be deposited along with natural sediments. Depending upon karst hydrology and water fluxes, the slurry may eventually reach karst springs heavily reducing water quality. Mineralogical composition of the sediments collected along karst waterways and springs shows variable proportions of calcite associated with dolomite and silicates particles whereas the marble powder samples from quarry areas are mainly composed by calcite grains. Cave deposits of natural origin have usually a fine-sand grain size whereas spring sediments have a more variable grain-size distribution. Marble powder mainly has a silt grain size and produces a sort of “granulometric and morphometric pollution” which influences the transport mechanism of solid load through the karst systems along both vadose and phreatic waterways.